Perbedaan dimensi vertikal pasien ortodonti 8 – 11 tahun menggunakan analisis jarabak berdasarkan jenis kelamin - Auliana Rahmadyah, Syazwina; Piona Sahelangi, Olivia (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Vertical facial dimensions affect craniofacial aesthetics and function. The Jarabak analysis is used to evaluate vertical facial proportions and assist in orthodontic diagnosis. Objectives: To analyze the differences in vertical dimensions among orthodontic patients aged 8–11 years based on gender using the Jarabak analysis at RSGM, Faculty of Dentistry, Universitas Trisakti. Methods: This study employed an observational analytic cross-sectional design with 80 cephalograms of males and females. A total of 80 samples were used, consisting of 40 males and 40 females aged 8–11 years. The parameters used were S-Go, N-Me, and the Jarabak ratio. To assess the differences in these measurements an independent T test was carried out for normally distributed data . Results: The results showed that the parameter values of Jarabak ratios for males and females do not have a statistically significant difference (p > 0.05). Jarabak ratio, the p value was obtained (0.928), in males the mean value ± SD was obtained (62.3 ± 3.) and in females (62.5± 4).Conclusion: This study concludes that the vertical facial dimensions in the population aged 8–11 years show no differences between males and females.